Influence of body buoyancy on the results achieved by 11-year-old children training swimming - Zaton, K.; Kwasna, A.; Chrobot, M.; Zysiak, B. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
The paper aims at addressing the question whether a high buoyancy level enables four-graders to perform better in swimming. Another problem is a dependency between a high level of lean body mass of swimmers and sports results achieved at 50 meters freestyle and butterfly. The research was conducted at the turn of 2001 and 2002 on a group of 37 four-graders of the swimming primary school in Wroclaw.